Improving the Ability of Tajwid Science in Reading the Qur'an - Vina Prabaningtyas; Imam Tabroni (Jurnal Pengabdian Masyarakat Bestari, 2022)
The Qur'an is the holy book of Muslims, which was revealed by Allah SWT to the Prophet Muhammad SAW. At the same time it becomes a miracle that is special from the others. The Qur'an was revealed in a certain period of 23 years Tajweed is giving a letter to its rights and order, returning the letter to the makhraj and origin (nature), and refining the pronunciation in the right way without being excessive (Jalal ad-Din as-Suyuthi, 2016: 102). The phenomenon that was obtained during field observations, by interviewing the principal of MDA Salman Alfarizi, he explained that 90% of children did not understand the law of recitation, only the most important thing was that children could recite the Koran less to discuss the law of recitation. To find out the increase in the ability of tajwid in reading the Qur'an at MDA Salman Alfarizi. The author chose to conduct descriptive quantitative research by visiting directly to the research location at MDA Salman Alfarizi to learn how to teach tajwid to students using the qira'ati method. The results showed that there was progress and improvement from the test, the material given. At the time of the Pre Test, Salman Alfarizi's MDA children only got an average score of 4.9 and were in the medium category, the average score increased to 7.5 during the Post Test from thirteen children and entered the high category.